Influence of Pre-Weld Heat Treatment and Aging Post-Weld Heat Treatment on Tensile Test and Microstructure of Aluminium 6061 Weld Joint - Herman Pratikno; Tin Rachmatullah; Hasan Ikhwani (International Journal of Offshore and Coastal Engineering (IJOCE), 2020)
Aluminium 6061 is an aluminium composition with Al-Mg-Si alloy which is often used for offshore structure material due to its high strength, good ductility and good corrosion resistance as well as its mechanical properties that can be enhanced by heat treatment. The purpose of this paper is to show the effect of heat treatment variations, in the form of preheating and aging PWHT, on tensile strength and microstructure of aluminium 6061 welding connection with GTAW process using electrode ER 5356. The pre-heat temperature variations used were 80°C, 100°C, and 120°C and the aging PWHT temperature variations used were 180°C and 260°c. The result shows that specimen with preheat treatment temperature of 120°C and aging pwht temperature of 260°C had the largest ultimate strength of 246.74 MPa and yield strength of 125.21 MPa. The highest percentage of Mg2Si formed was also found on the same specimen with a percentage of 48.84% in weld metal, 58.75% in HAZ, and 43.54% in base metal.